Fintech for the poor? Regulating the Kenyan digital credit market and its impact on borrowers - Minjin Kim; Maren Duvendack (Development Studies Research)
Digital credit claims to improve financial inclusion by providing loans to financially excluded populations, thus alleviating poverty. However, contrary to this claim, borrowers are often struggling with violations of consumer rights due to the absence of appropriate regulation. We investigate the case of Kenya where the Central Bank of Kenya Amendment Bill 2021 was introduced to solve consumer protection issues raised by the digital credit industry. In this paper, we draw on qualitative interviews finding that digital credit consumers are being unfairly treated. Consumers are suffering from default and blacklisting, aggressive debt collection practices that cause mental distress, exorbitant interest rates, and unlicensed lenders. In addition, there are problems with the transparency and effectiveness of digital credit due to deceptive marketing and the infringement of data privacy. Finally, this study reveals that the Central Bank of Kenya Amendment Bill 2021 leaves significant gaps to be addressed with some elements of the bill potentially putting borrowers at risk.